Laparoscopic Radical Prostatectomy: The Learning Curve of a Low Volume Surgeon - Anuar I. Mitre; Mario F. Chammas; José Eugênio A. Rocha; Ricardo Jordão Duarte; Gustavo Xavier Ebaid; Flavio Trigo Rocha (The Scientific World Journal)
Objective. Analyze the learning curve for laparoscopic radical prostatectomy in a low volume program. Materials and Methods. A single surgeon operated on 165 patients. Patients were consecutively divided in 3 groups of 55 patients (groups A, B, and C). An enhancement of estimated blood loss, surgery length, and presence of a positive surgical margin were all considered as a function of surgeon’s experience. Results. Operative time was 267 minutes for group A, 230 minutes for group B, and 159 minutes for group C, and the operative time decreased over time, but a significant difference was present only between groups A and C (). Mean estimated blood loss was 328 mL, 254 mL, and 206 mL (). A conversion to open surgery was necessary in 4 patients in group A. Positive surgical margin rates were 29.1%, 21.8%, and 5.5% (). Eight patients in group A, 4 patients in group B, and one in group C had biochemical recurrence. Conclusion. Significantly less intraoperative complications were evident after the first 51 cases. All other parameters (blood loss, operative time, and positive surgical margins) significantly decreased and stabilized after 110 cases. Those outcomes were somehow similar to previous published series by high-volume centers.